2020
DOI: 10.1097/sla.0000000000003014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Hepatocellular Carcinoma With Bile Duct Tumor Thrombus

Abstract: Objective: To identify optimal surgical methods and the risk factors for long-term survival in patients with hepatocellular carcinoma accompanied by macroscopic bile duct tumor thrombus (BDTT). Summary Background Data: Prognoses of patients with hepatocellular carcinoma accompanied by BDTT have been known to be poor. There have been significant controversies regarding optimal surgical approaches and risk factors because of the low incidence and small nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 29 publications
4
43
1
1
Order By: Relevance
“…Tumour thrombectomy is believed to have potential risks of peritoneal dissemination and recurrence in the preserved bile duct. However, Kim et al ( 37 ) proclaimed that thrombectomy does not significantly increase the risk of peritoneal metastasis. None of the patients who underwent tumour thrombectomy presented with peritoneal dissemination in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour thrombectomy is believed to have potential risks of peritoneal dissemination and recurrence in the preserved bile duct. However, Kim et al ( 37 ) proclaimed that thrombectomy does not significantly increase the risk of peritoneal metastasis. None of the patients who underwent tumour thrombectomy presented with peritoneal dissemination in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of bile duct resection for patients with HCC and BDTT may cause recurrence due to direct invasion of the tumour into the bile duct, periductal capillary plexus and lymphatic system ( 27 , 38 ). Recently, a multicentre study reported that bile duct resection was a significant favourable prognostic factor for recurrence, OS and survival after recurrence ( 37 ). Based on the aforementioned studies, the selection criteria for resecting the bile duct could not be too absolute, and an individualized treatment plan was required according to the condition of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…The primary treatment strategy for HCC is to remove the tumor by surgery, but HCC may relapse after the operation. It was reported that the 5-year recurrence rate of HCC after surgery was 74.2% in Japan and Korea 54. Therefore, post-operational monitoring and precise prognosis are necessary for cancer treatment.…”
Section: Prognosis and Post-operational Monitoring Of Hccmentioning
confidence: 99%
“…3 Of these causes, BDTT is a rare but special clinical feature of HCC, with the incidence rate of only 1-9%. [4][5][6] With regard to the management of HCC with BDTT, surgical resection has become the main treatment method. Numerous literature have reported that surgical resection can result in better curative effect and improve long-term survival of patients compared to other palliative-intent therapy.…”
Section: Introductionmentioning
confidence: 99%